The Role of an Inclusive Environment in Improving Early Childhood Executive Function Skills - Roby Naufal Arzaqi; Aisah Karunia Rahayu; Deri Hendriawan (Indonesian Journal of Early Childhood Education Studies, 2024)
This study aims to explore the role of an inclusive environment in supporting the development of Executive Function (EF) skills in early childhood. EF is needed to face modern challenges that require critical thinking, problem-solving, and emotional regulation. However, challenges such as the lack of teacher training and adaptive educational resources hinder EF's optimal development. This study uses a qualitative method with a case study design. Through in-depth interviews with three ECCE teachers then analysed using thematic analysis, the study found that although an inclusive environment provides a great opportunity to develop EF, there is an urgent need for further support, both in teacher training and educational facilities. An inclusively designed environment not only supports social development, but also creates ideal conditions for the development of EF skills in early childhood, especially children with special needs. The results of this study are expected to contribute to improving EF skills and encouraging the application of inclusion principles more effectively in early childhood education.